The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1177/1940082918755513
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Differentiation and Fragmentation in Response to Climate Change of the Narrow EndemicPsittacanthus auriculatus

Abstract: The state of Oaxaca is positioned in a rather unique biogeographical position with the highest diversity of vascular plants in Mexico. The isolation of xeric valleys surrounded by complex mountain ranges in Oaxaca supplies an excellent opportunity to investigate the influence of the Pleistocene events on xeric species. To test for the alternative hypotheses of Pleistocene glacial refugia, we used sequences of two chloroplast markers to examine the phylogeographic patterns of the endemic mistletoe species Psitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 91 publications
5
12
0
Order By: Relevance
“…Increase in temperature, shifts in precipitation patterns, and the increasing occurrence of extreme weather events jeopardize the persistence of species and their ecosystems due to its potential to affect areas far from human settlements (IPCC, 2014; Malcolm et al, 2006). Current climate change is already altering the geographic distribution of plant and animal species and several others are expected to increase/decrease and/or to shift their geographic distribution in response to climate change (Borzée et al, 2019; Freeman et al, 2019; Mendoza-González et al, 2013; Ornelas et al, 2018). Studies carried out with distribution data (1967 to 2002) of 56 bird species showed that birds with northern distributions across the temperate northern hemisphere are not expanding their ranges southward due to global warming (Hitch & Leberg, 2007; Thomas & Lennon, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increase in temperature, shifts in precipitation patterns, and the increasing occurrence of extreme weather events jeopardize the persistence of species and their ecosystems due to its potential to affect areas far from human settlements (IPCC, 2014; Malcolm et al, 2006). Current climate change is already altering the geographic distribution of plant and animal species and several others are expected to increase/decrease and/or to shift their geographic distribution in response to climate change (Borzée et al, 2019; Freeman et al, 2019; Mendoza-González et al, 2013; Ornelas et al, 2018). Studies carried out with distribution data (1967 to 2002) of 56 bird species showed that birds with northern distributions across the temperate northern hemisphere are not expanding their ranges southward due to global warming (Hitch & Leberg, 2007; Thomas & Lennon, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…These are projected across landscapes, and therefore, might be helpful when acquiring occurrence data on the distribution of species is not achievable, or when the ecological variables related to the distribution of the species had changed (Borzée et al, 2019; Freeman et al, 2019; Guisan & Thuiller, 2005). SDMs have been widely used to predict the potential distribution as a function of climate change in several organisms (Borzée et al, 2019; Kafash et al, 2018; Ornelas et al, 2018; Ramírez-Preciado et al, 2019), including birds, in which SDMs were effective to predict their current and future distribution (Atauchi et al, 2020; Freeman et al, 2019; Townsend Peterson et al, 2001; Prieto-Torres et al, 2020; Şekercioğlu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In plants, higher genetic diversity has been frequently found in zones that had a stable climate during glacial periods and for which post-glacial migration was identified (Faye et al, 2016; Wolfe et al, 2016), and in contrast, unstable regions are expected to represent recently colonized areas and thus exhibit lower genetic diversity (Abellán & Svenning, 2014; Caze et al, 2016; Ornelas, Licona-Vera & Vásquez-Aguilar, 2018). Higher genetic diversity has been found as well in environments that fluctuate in time or space, in which different genotypes can be favored at different times or locations and shifting selection can support higher genetic variation in fitness, even when stabilizing selection is acting to reduce genetic variation (Nadeau, Urban & Bridle, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Also, wild animals will need more water during droughts since they will have to rely more on evaporative cooling to remove extra heat (Turner et al, 2022). Furthermore, changes in species' geographic ranges, growing seasons, reproductive phenology, primary production, and diversity are among the anticipated effects of climate change on water supplies (Fonseca, 2022;Habibullah et al, 2022;Moullec, 2022;Numata et al, 2022;Ornelas et al, 2018). Thus, any change in water resources (i.e., quantity and quality) brought on by the effects of climate change on precipitation might result in biodiversity loss (Fonseca, 2022;Habibullah et al, 2022;Nyembo et al, 2022); change in animal behaviour and physiology (Turner et al, 2022); and many other negative impacts (Table 1).…”
Section: Implication Of Climate Change On Biodiversitymentioning
confidence: 99%